Leaf Production and Dry Matter Accumulation In Radish (Raphanus sativus L.) to Different Levels of Organic Manures and Inorganic Fertilizer in Sand Regosol - Deshika Viraji M. W; Brintha Karunarathna (International Journal of Economic Plants)
Chemical fertilizers are applied to increase leaf related parameter, but it causes the adverse effect on soil environment and human health. To assess the comparative response of different level of organic manures and inorganic fertilizers on leaf production and dry matter accumulation in radish (Raphanus sativus L.) in Sandy Regosol, field experiment was conducted at the crop farm, Eastern University, Sri Lanka in 2018. The experiment was laid out using Randomized Complete Block Design (RCBD) with seven treatments and four replicates. Treatments were recommended inorganic fertilizer, and 8 t ha-1, 6 t ha-1, 4 t ha-1 and 2 t ha-1 cow dung with 2 t ha-1, 4 t ha-1, 6 t ha-1 and 8 t ha-1 compost as a basal and ½ dose of recommended fertilizer as a top dressing and 10 t ha-1 cowdung and 10 t ha-1 compost as a basal and ½ dose of recommended fertilizer as a top dressing. The present study suggested that different levels of cowdung and compost as a basal with half dose of inorganic fertilizer as top dressing gave similar results compared with recommended inorganic fertilizer in leaf development and dry matter accumulation in radish in sandy regosol.